The quiet transnationalisation of board-level employee representation in national law and practice: A case for pan-European legislation - Sara Lafuente (European Trade Union Institute (ETUI), 2023)
Board-level employee representation rights are far from harmonised at the level of the European Union. Yet, beyond some limited cases of Europeanisation taking root in EU secondary law (i.e. the European Company Directive (Societas Europaea) and other corporate law instruments taking this framework as a reference), experiences of transnationalisation have found their way in multinational groups operating in the European Economic Area based on national law and practice and independently of any EU legislation. This Working Paper examines the diversity of institutional routes available and applied by actors in Germany, Sweden, Norway, Denmark and France. It argues that the legal, practical and political challenges raised by these bottomup solutions call for pan-European coordinated solutions on representation rights, both in legislation and trade union strategy. Drawing on country case studies and interdisciplinary methods, the Paper identifies different practices of transnationalisation and the factors which promote or hinder them, as well as the implications for national systems of employee representation and the development of European industrial relations. Some recommendations emerge for trade unions, policymakers and research.
Keywords: 330; board-level employee representation; Europeanisation; transnationalisation; MNCs; trade unions